Pengaruh Intellectual Capital Terhadap Return Saham Dengan Profitabilitas Sebagai Variabel Intervening - Fazrin, Rizki; Hermanto, Hermanto; Putra, I Nyoman Nugraha Ardana (E-Jurnal Akuntansi; Vol 29 No 1 (2019), 2019)
The study aims to analyze the indirect influence of Intellectual Capital and Stock Return through profitability. Banking companies listed in Indonesia Stock Exchange 2013-2017 period. Samples were determined by purposive sampling obtained 145 samples. Data analysis tools using Path Analysis. Intellectual capital research findings showed no positive effect on stock returns over profitability as an intervening variable. As the research implications for consideration by the regulator in the field of accounting on the importance of intellectual capital information so that the regulation needs to be made on how to measure, recognize and report it. Keywords : Intellectual Capital, Stock Return, Profitability